Economic Policy Uncertainty and Dynamic Capital Structure Evidence from China Manufacturing Industry - Wang, Zhenze (2020)
Applying the economic policy uncertainty (EPU) index, this study base on eight to ten years data of Chinese manufacturing industry to discuss the effect of EPU on the capital structure, capital structure adjustment speed, and using the mediating effect model to confirm EPU realising its effect through affects firm capital investment and bank credit growth rate. The fixed-effects model, instrumental variable method and system GMM estimation shows a negative effect of EPU on capital structure and its adjustment speed, and these effects seem strong than we think. The mediation effect model proves the effectiveness of the above two channels. Further, the effect of EPU on capital structure is varying across firm size and firm leverage level. This paper highlights the importance of EPU in the capital structure.